CATATAN LAPANGAN MENGENAI SATWALIAR DI LOKASI EKOWISATA SYURGAR SAUSAPOR, KABUPATEN TAMBRAUW - Fatem, Sepus; Worabai, Meliza S; Beljai, Matheus; Wanma, Alfredo O; Ungirwalu, Antoni; Runtuboi, Yubelince; Dian Nebore, Idola; M Jitmau, Anjeli; Ayomi, Adomina; S Erari, Semuel (Jurnal Belantara, 2024)
This study was conducted at Syurgar ecoutourism site, subdistrict of Sausapor Tambrauw district. Data was collected from June to July 2020 using survey method, direct catching, cage trap and interview. This study aimed to list the wildlife species, especially Birds, Mammals Herpetofauna, and Butterflies in order to complete data of the government of Tambrauw District for the purpose of Syurgar ecotourism development. This study recorded that there were 15 birds’ species of 13 families, 12 mammals’ species of 6 family, 4 herpetofauna’s species of 4 families, and 25 butterflies of 4 families. Syurgar has a potential to be a birdwatching site. There are several appealing birds, including Lesser bird-of-paradise (Paradisaea minor), king bird of paradise (Cincinurus regius), blyth’s hornbill (Rhyncetores plicatus), sulphur-crested cockatoo (Cacatua galerita). Endemic species of mammals include long-beaked echidna (Zaglosus bruijnii), dorcopsis/forest’s wallaby (Dorcopsis sp.), northern common cuscus (Phalanger orientalis), common spotted cuscus (Spilocuscus maculates), old world fruit bats (Dobsonia sp.), great flying fox (Pteropus neohibernicus). Endemic species of herpetofauna include frogs (Papurana sp.), Papua wrinkled ground frog (Cornufer papuensis). Eventually, some butterflies’ species include redeye bushbrown (Mycalesis aethiops), bushbrown (Mycalesis elia), and Papuan gull (Cepora abnormis). It is strongly suspected that several birds, mammals, herpetofauna, and butterflies have not been recorded due to time constraints. Therefore, further study is recommended for data completion.